Usulan Perbaikan Keseimbangan Lini di PT. XYZ Menggunakan Moodie-Young dan Ranked Positional Weight untuk Meningkatkan Efisiensi Lini Produksi - sriwana, iphov kumala; Jatikusumo, Amarilis; Erni, Nofi; Suwandi, Arief; Rachman, Taufiqur (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
PT. XYZ is a company that produces X shoes. To meet customer needs, it is necessary to design an effective and efficient production line. The problem experienced by the company is that the production target has not been achieved, which is 80 pairs per hour. The daily output that is achieved is less than the predetermined production target, so it is necessary to analyze the line balance. The purpose of this analysis is to determine the causes of not achieving production targets, to determine the value of line efficiency, balanced delay, and smoothness index for each method and to get the right proposal for the company. The research was conducted by describing precedence diagrams and collecting time data from each work element then testing and calculating the standard time, following which line balancing was carried out using the Ranked Positional Weight and Moodie-young. From the calculation results, the results obtained a better line balance using the Moodie-young method, namely, an increase in line efficiency by 27.45% from 57.67% to 85.12%, a decrease in balanced delay by 25.09% from 39.97%. to 14.88%, and a decrease in the smoothness index of 39.55 from 62.62 to 23.08. In addition, there was a decrease in the number of operators working by 2 people, from 16 operators to 14 operators and a reduction in the existing work stations (SK) by 4 SK, from 12 SK to 8 SK.